2018 IEEE Conference on Decision and Control (CDC) 2018
DOI: 10.1109/cdc.2018.8619609
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Relaxation of Unit Commitment with AC Transmission Constraints

Abstract: This paper proposes a sequential convex relaxation method for obtaining feasible and near-globally optimal solutions for unit commitment (UC) with AC transmission constraints. First, we develop a second-order cone programming (SOCP) relaxation for AC unit commitment. To ensure that the resulting solutions are feasible for the original non-convex problem, we incorporate penalty terms into the objective of the proposed SOCP relaxation. We generalize our penalization method to a sequential algorithm which starts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…The success of the sequential framework and penalization in solving bilinear matrix inequalities (BMIs) demonstrated in [36,38,39]. The incorporation of penalty terms into the objective of SDP relaxations are proven to be computationally effective for solving non-convex optimization problems in power systems [52,53,84,85]. These papers show that penalizing certain physical quantities in power network optimization problems such as reactive power loss or thermal loss facilitates the recovery of feasible points from convex relaxations.…”
Section: Comprehensive Boundary Propertymentioning
confidence: 99%
“…The success of the sequential framework and penalization in solving bilinear matrix inequalities (BMIs) demonstrated in [36,38,39]. The incorporation of penalty terms into the objective of SDP relaxations are proven to be computationally effective for solving non-convex optimization problems in power systems [52,53,84,85]. These papers show that penalizing certain physical quantities in power network optimization problems such as reactive power loss or thermal loss facilitates the recovery of feasible points from convex relaxations.…”
Section: Comprehensive Boundary Propertymentioning
confidence: 99%
“…Another single convex model worth citing is that proposed in the work of Fattahi et al [3] for the DC network-constrained UC problem, in which reformulation-linearization is used to introduce relaxed non-convex quadratic inequalities in order to tighten the SDP relaxation seeking to avoid local feasibility resolution. More recently, Zohrizadeh et al [26] propose a power loss penalization method based on a series of SOCP relaxations that require an initialization "sufficiently close to the feasible set" for convergence.…”
Section: Related Workmentioning
confidence: 99%
“…Researchers have proposed various methods to increase the computational tractability of the AC-UC problem using, for example, Lagrange relaxation [19], decomposition [18], [20], and convexification methods [21]. However, this is an ongoing research area without a singular superior solution technique identified yet.…”
mentioning
confidence: 99%